Motif Konflik Sosial dalam Novel Laut Bercerita Karya Leila S. Chodori : Kajian Sosiologi Sastra: Social Conflict Motifs in the Novel Tales of the Seaby Leila S. Chudori: A Sociological Study of Literature - Sijabat, Asnita; Marsella, Emma; Kudadiri, Amhar (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
Conflict is a social process between two or more people who have their own interests and goals. Where one party tries to get rid of the other party by destroying it. Social conflict is a dispute or dispute that often occurs in society and has a perception of differences in interests or beliefs. Every individual definitely has their own goals and interests so that social conflict is an inevitable part of society. In studying and analyzing social conflict in literary works, another science is needed, namely literary sociology. This research aims to describe the motif of social conflict contained in the novel Laut Bercerita by Leila S Chudori. In analyzing the novel Laut Bercerita, the research used is literary sociology. The method used in this research is a qualitative descriptive method. The qualitative descriptive method produces data in the form of words in the form of quotationsas problem solving. Based on the data results, motiv 2 triggers for social conflict were obtained from the concept of conflict theory according to Lewis A Coser in the Novel Laut Bercerita, namely: 1) realistic social conflict and 2) non-realistic conflict